2022
DOI: 10.1007/s00432-022-04098-8
|View full text |Cite
|
Sign up to set email alerts
|

Blood group antigens SLeX, SLeA, and LeY as prognostic markers in endometrial cancer

Abstract: Purpose Endometrial cancer (EC) is the most common gynecological cancer worldwide. Treatment has been improved in recent years, but, in advanced stages, therapeutical options are still limited. It has been reported that the expression of the blood group antigens Sialyl Lewis X (SLeX), Sialyl Lewis A (SLeA) and Lewis Y (LeY) is associated with prognosis in several tumors. Large studies on endometrial and cervical cancer are still pending. Methods Specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Regarding this result, we can speculate about an enzymatic complex comprising both enzymes, essential for protein Lewis X sialylation in LS174T cells. SLeX expression in cancer has been associated with patient's invasive tumors and dismal prognosis [12,41], and for this reason, one of our objectives was to evaluate the biological impact of inhibiting SLeX biosynthesis in selected GI cancer cells. We observed that SLeX inhibition did not affect cancer cell proliferation overall.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding this result, we can speculate about an enzymatic complex comprising both enzymes, essential for protein Lewis X sialylation in LS174T cells. SLeX expression in cancer has been associated with patient's invasive tumors and dismal prognosis [12,41], and for this reason, one of our objectives was to evaluate the biological impact of inhibiting SLeX biosynthesis in selected GI cancer cells. We observed that SLeX inhibition did not affect cancer cell proliferation overall.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are still some weakness. First, as this study focuses on routine laboratory biomarkers, some prognostic markers were not included, such as tumour sizes and blood group antigens [ 31 , 32 ]. In addition, histopathological evaluation has a strong association with EC prognosis and is generally taken as a cornerstone for EC classification.…”
Section: Discussionmentioning
confidence: 99%
“…SLeX expression in cancer has been associated with patient’s invasive tumors and dismal prognosis [ 12 , 43 ], and for this reason, one of our objectives was to evaluate the biological impact of inhibiting SLeX biosynthesis in selected GI cancer cells. We observed that SLeX inhibition did not affect cancer cell proliferation overall.…”
Section: Discussionmentioning
confidence: 99%